2017
DOI: 10.1016/j.jclepro.2017.05.200
|View full text |Cite
|
Sign up to set email alerts
|

Examining industrial structure changes and corresponding carbon emission reduction effect by combining input-output analysis and social network analysis: A comparison study of China and Japan

Abstract: Examining industrial structure changes and corresponding carbon emission reduction effect by combining input-output analysis and social network analysis: A comparison study of China and Japan, (2017),

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
54
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 138 publications
(64 citation statements)
references
References 40 publications
(35 reference statements)
3
54
0
Order By: Relevance
“…Okamoto [23] investigated the effect of a structural transition to the service industry in Japan using decomposition analysis, and he documented that the service industry reduced CO 2 emissions in Japan over the period 1995-2005. Li et al [64] applied an input-output model and social-network analysis in a comparative study of Japan and China. They argued that industrial adjustment and connectivity among various industries is improving in China, but its industrial transition process still needs to be improved to mitigate CO 2 emissions as Japan moves more toward the service sector.…”
Section: Structural Change Studiesmentioning
confidence: 99%
“…Okamoto [23] investigated the effect of a structural transition to the service industry in Japan using decomposition analysis, and he documented that the service industry reduced CO 2 emissions in Japan over the period 1995-2005. Li et al [64] applied an input-output model and social-network analysis in a comparative study of Japan and China. They argued that industrial adjustment and connectivity among various industries is improving in China, but its industrial transition process still needs to be improved to mitigate CO 2 emissions as Japan moves more toward the service sector.…”
Section: Structural Change Studiesmentioning
confidence: 99%
“…Therefore, we referred to previous studies and the basic influence mechanisms of the variables when determining the constraints. Apparently, changes in urbanization are mostly caused by demographic changes [21,22], while transformations in industrial structure are often caused by policies, investments, and technology [11,15,16]. Moreover, a time lag in the impact of industrial structure on urbanization cannot be ruled out because tertiary industry appears to be expanding rapidly and disorderly, and it cannot match the urbanization plan in China.…”
Section: Identification Of Constraintsmentioning
confidence: 99%
“…Djankov et al used the gravity model to empirically analyze the changes in trade flows between the nine Russian regions of the former Soviet Union and the three former Soviet republics from 1987 to 1996 [11]. Li et al compared changes in the industrial structure of China and Japan by combining input-output analysis with social network analysis [15]. Wang et al studied the spatial linkages of the urban economy for the Pearl River Delta in China from the perspective of industry, based on the urban flow intensity model [16].…”
Section: Introductionmentioning
confidence: 99%
“…Although these studies have showed insightful findings and made great contributions to the study of regional economy, they often focused on the external spatial interaction of regional economy, with few taking into account the complex internal economic linkages between different industrial sectors at the regional level. In the existing research, the input-output theory is a popular method to study the interactions between different sectors of a region [9,15,[17][18][19]. For example, Shi et al explored the inter-sectoral relations between five provinces of the Inland River Basin in China by adopting input-output analysis, but these studies did not measure the industrial interaction among provinces [18].…”
Section: Introductionmentioning
confidence: 99%